التنظيم القانوني لحدود الأقاليم الفدرالية وآليات تسوية المنازعات الحدودية في الدولة الفدرالية "دراسة تحليلية مقارنة" - قادر, سوزان عثمان; عزم, لائق محمدعزيز (Sulaimani Journal for Humanities, 2022)
This research has made a living legal topic into a research subject within the framework of the federal state, because with the creation of the federal state, many problems specifically relating to this type of country will arise. For instance, the problem of creating a federal state or the problem of distributing powers and wealth between the federal government and the regionals government, in the end the problems related to the internal borders of the country and solving those border conflicts. The federal state consists of several regions, these regions have their own independent borders and those borders are constitutional and administrative, and the regions follow their own characteristics and constitutional powers within the boundaries they have. There is more than one region the federal state, which means there is more than one local border, resulting in border disputes within the federal state. These border disputes also require constitutional and legal arrangements and methods of solution. From its inception in 1921 until 2003, Iraq was a simple state, distinguished by having the union of internal and external sovereignty, after the invasion of Iraq by the international coalition led by the United State of America in 2003 along with writing the constitution of Iraqi republic in 2005, Iraq transformed from a simple state into a democratic, pluralistic federal state, in which power was divided between the federal government, the regional government and the province, this change in the form of Iraqi state caused many problems and battlefields, one of the most obvious is the border problem and border conflict between Kurdistan Region and Iraqi federal government. The constitution of the Republic of Iraq in 2005 dealt with the border issue between the Kurdistan Region and the Iraqi Federal government and included this issue in the name of (Disputed Territory). The disputed territory is the battleground of a real problem facing the federal system in Iraq; this issue needs a brave and objective confrontation within the framework of the constitutional road map drawn up in 2005 Iraqi constitution. It cannot tolerate wasting time and leaving to the future, on the contrary, it means extending the age of a problem which became to exist with the establishment of Iraq in 1921 and the failure of the Iraqi federal experience as expected. This study consists of two topics; the first is "the subject of constitutional and legal organization of the formation of federal regions and the technique of determining the borders of the regions in Iraq" it is a research subject. In the second topic, "the border disputes within the federal state and the method of amending the borders of the regions" it is the subject of discussion and consideration. In addition to, the research begins with a scientific introduction and ends with a number of conclusions and recommendations that the researcher has reached as a result of his research